LITERATURE REVIEW : HUBUNGAN AKTIVITAS FISIK DENGAN DISMENORE PRIMER PADA REMAJA - Santha Eliska Br Gurusinga; Austin Bertilova Carmelita; Arif Rahman Jabal (Fakultas Kedokteran, Universitas Palangka Raya, 2021)
Dysmenorrhea often occurs in adolescents because the hormones produced are not yet stable. The prevalence of primary dysmenorrhea in Indonesian adolescents is 60-75%. Physical activity is one of the primary risk factors for damage. Youth physical activity decreases every year. Purpose: This literature review aims to analyze the relationship between physical activity and primary dysmenorrhea in adolescents. Methods: The data search engines used were Google Scholar, Science Direct, and Garuda. The journals collected are national and international journals from 2015-2020. Search for research articles using inclusion and exclusion criteria. The literature review uses 15 national journals and 8 international journals. Results: The journals that stated physical activity related to primary in adolescents were found as many as 21 journals, while 2 journals that were not related. Physical activity increases endorphins, increases blood flow to the genitals, and increases vasodilation of blood vessels. Conclusion: Physical activity is related to primary in adolescents.